Impact of Substrate Biasing During AlN Growth by PEALD on Al2O3/AlN/GaN MOS Capacitors. Issue 5 (28th December 2021) - Legallais, Maxime; Lefevre, Gauthier; Martin, Simon; Labau, Sébastien; Bassani, Franck; Pélissier, Bernard; Baron, Thierry; Vauche, Laura; Le Royer, Cyrille; Charles, Matthew; Vandendaele, William; Plissonnier, Marc; et al.
Abstract: In this article, the role of the substrate biasing during the passivation of GaN with AlN deposited by plasma enhanced atomic layer deposition (PEALD) is investigated. In addition to a commonly used remote inductively‐coupled plasma source, the PEALD reactor is equipped with another power supply allowing the substrate to be biased and to adjust the ion energy impinging on the substrate surface. The presence is reported of a narrow bias window where the GaN passivation is significantly improved compared to a standard AlN film deposited without bias. It is found that the AlN film quality is enhanced and the crystallographic structure changes from a well‐ordered epitaxial relationship with the GaN substrate to textured films when applying a bias. Finally, the capacitance–voltage characteristics ( C–V ) of Al2 O3 /n‐GaN and Al2 O3 /AlN/n‐GaN metal‐oxide‐semiconductor (MOS) capacitors are also studied. It is shown that the addition of an AlN interlayer deposited with the appropriate bias is essential to positively shift the flatband voltage of the C–V characteristics while preserving high AlN/n‐GaN interface quality. Therefore, the GaN passivation with AlN deposited using substrate biasing provides a promising pathway towards the manufacturing of normally‐off MOS‐channel high electron mobility transistors. Abstract : The presence of a narrow bias window is reported where the GaN passivation is significantly improved compared to a standard AlN film deposited without bias. It is shown that the addition of an AlN interlayer deposited with the appropriate bias is essential to positively shift the flatband voltage of the C–V characteristics while preserving high AlN/n‐GaN interface quality.